2018
DOI: 10.1002/dev.21780
|View full text |Cite
|
Sign up to set email alerts
|

Long‐chain polyunsaturated fatty acid supplementation in the first year of life affects brain function, structure, and metabolism at age nine years

Abstract: The present study sought to determine whether supplementation of long-chain polyunsaturated fatty acids (LCPUFA) during the first year of life influenced brain function, structure and metabolism at 9 years of age. Newborns were randomly assigned to consume formula containing either no LCPUFA (control) or formula with 0.64% of total fatty acids as arachidonic acid (ARA; 20:4n6) and variable amounts of docosahexaenoic acid (DHA; 22:6n3) (0.32%, 0.64%, or 0.96% of total fatty acids) from birth to 12 mo. At age 9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 43 publications
2
44
0
1
Order By: Relevance
“…On sustained attention in the first year of life, a test of rule learning requiring inhibition between 3 and 5 years, and on verbal IQ at 5 and 6 years of age, the children fed formulas with a DHA to ARA ratio of 0.5:1 and 1:1, but not the group fed a ratio of 1.5:1, performed significantly better than the no LCPUFA group. Brain evoked response potentials to a test of inhibition (Go-No Go task) at 5.5 years and brain imaging studies at 9 years were consistent with these results (48,49).…”
Section: Ratio Of Dha To Ara In Formula Influences N-6 Lc-pufa In Brasupporting
confidence: 69%
“…On sustained attention in the first year of life, a test of rule learning requiring inhibition between 3 and 5 years, and on verbal IQ at 5 and 6 years of age, the children fed formulas with a DHA to ARA ratio of 0.5:1 and 1:1, but not the group fed a ratio of 1.5:1, performed significantly better than the no LCPUFA group. Brain evoked response potentials to a test of inhibition (Go-No Go task) at 5.5 years and brain imaging studies at 9 years were consistent with these results (48,49).…”
Section: Ratio Of Dha To Ara In Formula Influences N-6 Lc-pufa In Brasupporting
confidence: 69%
“…Previous studies have suggested that DHA and EPA may protect against peroxidation and the effects of age-related brain pathology (Hasadsri et al, 2013;Chen et al, 2017). Lipids are involved in cellular signaling, energy balance, blood-brain barrier (BBB), and inflammation (Song et al, 2008;Willis et al, 2009), and such age-dependent lipidome changes that disrupt these functions may contribute to neurodegenerative diseases (Arnoldussen et al, 2016;Bos et al, 2016;Hooper et al, 2018;Luo et al, 2018;McNamara et al, 2018;Lepping et al, 2019), such as Alzheimer's disease (AD) (Schmitt et al, 2014;Hussain et al, 2019).…”
Section: Factors That Affect Brain Lipids Demographic Factors That Inmentioning
confidence: 99%
“…Follow-up at 9 years demonstrated effects on brain structure, function, and neurochemical concentrations. The group with 1:1 supplementation had greater connectivity between pre-frontal and parietal regions, and groups with 2:1 and 1:1 supplementation had greater white matter volume in regions associated with attention and inhibition (70). Results from the other center in the DIAMOND study demonstrated higher MDI, higher emotional regulation scores and higher language scores when all supplemented groups were compared to the control group (71).…”
Section: Fatty Acid Ratio and Neurodevelopment In Term Infantsmentioning
confidence: 83%